الإنفاق الإعلاني في سورية دراسة تحليلية - ديوب, محمد; برهوم, أديب; خوندة, عبد الكريم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر حجم الإنفاق الإعلاني مؤشراً جيداً على الحالة التي يعيشها اقتصاد أي بلد سواء في الكساد أو في الازدهار، كما يشير اتجاه ذلك الإنفاق إلى طبيعة الاقتصاد السائد فيما إذا كان استهلاكياً أم منتجاً. لذا تعتبر دراسته وتحليله أمراً مفيداً للوقوف على توصيفٍ متكامل للاقتصاد السوري الذي يعتبر أنه ريعيٌ بالغالب ويعيش حالةً مستقرة منذ سنوات. وقد حان الوقت لبناء صناعة إعلانية قوية تمتلك بعداً استراتيجياً بالاعتماد على إنفاقٍ إعلانيٍ رشيد يساعد الاقتصاد السوري على مواجهة تحديات عصر العولمة التجارية الجديد؛ الذي تنعدم فيه الحدود أمام توسع الشركات التجارية العالمية المدعومة بإنفاقٍ إعلاني مرتفع، وتقل فيه أهمية المواصفات المادية بين السلع المتنافسة أمام الأهمية المتزايدة للقيمة المضافة والعلامات التجارية العالمية. وغير ذلك لن يكون أمام المنتجات الوطنية إلا أن تسلك الطريق نفسه وتسعى لحجز موقع لها في السوق الدولية معتمدةً على إنفاق إعلاني فعال. Advertising spending is considered a good indicator on the situation that any economy lives either in depression or prosperity, as it indicates the quality of the prevailing economy, whether producing or consuming. Therefore, studying and analyzing advertising spending are good to obtain an integrated description of the Syrian economy, which is almost known as yielded and stable economy for years. The time has come to build a strong advertising industry with a long-term strategy, depending on rational advertising spending. This helps the Syrian economy in beating the challenges of the new era of globalization, in which expanding international trade companies supported by high advertising spending do not recognize traditional boundaries, and where the material specifications decrease among the competing products for the sake of international trade marks and additional values. At that time, the national trade marks would be in great need to follow the same way in order to have a share in the world market, depending on effective advertising spending.